The World Wide Web – An Interactive Educational Environment - Tan, Desney; Szczerba, Robert J; Jr., John J Uhran ((1996) Tenth Annual Midwest Computer Conference, 1996)
At the University of Notre Dame, we are currently implementing, while constantly developing, this new state-of-the-art electronic classroom. We do this in the hope of utilizing our resource base to provide for a productive and complete education. Much work has yet to be done. We hold the future in our hands; we may decide to ride the information wave, using it to its fullest potential, or we may choose to allow it to race past us, never to be seen again. May the latter never be our fate.